Sưu tập văn nghệ : 1948 - 1954: 56 số tạp chí văn nghệ xuất bản trong kháng chiến tại Việt Bắc. (Hội nhà văn, 1999)
Sưu tập văn nghệ 1948 - 1954.( 56 số tạp chí văn nghệ xuất bản trong kháng chiến tại Việt Bắc)